Coping Strategies for English Language Anxiety: A Comparative Study of Lecturers and Students Across Disciplines - Dewi Warna; Muhamad Uyun (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the efficacy of coping strategies for English language anxiety among lecturers and students within religious and general study programs, employing a mixed-methods approach that integrates quantitative T-tests and qualitative interviews. Results indicate significant differences in the anxiety-coping strategies between lecturers and students, with distinct variations across the two types of study programs. While strategies among religious and general program lecturers showed no significant differences, a marked contrast was observed between students of these programs, highlighting the influence of disciplinary context on anxiety management. The study reveals that lecturers and students successfully use tailored strategies to mitigate language anxiety, suggesting the importance of contextualized approaches. Based on these findings, it is recommended that educational institutions develop specific training programs that enhance the capability of educators and students to manage language anxiety effectively. Such programs should focus on communication techniques, psychological resilience, and cultural awareness, which are crucial in diverse academic environments. The implications of this research support a differentiated approach to language education policy, advocating for interventions sensitive to the unique challenges and needs of various academic disciplines.